Elucidation of genetic diversity in hawthorn (Crataegus azarolus L.) accessions naturally growing in the Eastern Mediterranean region of Türkiye using morphological, pomological, and inter simple sequence repeat markers - Yazgan Tunç; Mehmet Yaman; Kadir Uğurtan Yılmaz; Ali Khadivi; Somayeh Goodarzi (BMC Plant Biology)
Abstract Background Türkiye hosts many important fruit species due to its geographical location and ecology. Hawthorn, which is highly beneficial for human health, is one of these significant fruit species. In the present study, 125 accessions of Crataegus azarolus L. were identified from different regions of hawthorn germplasm in the Eastern Mediterranean region of Türkiye in 2022 and 2023. This study was conducted to detect the morphological, pomological, and molecular genetic variations of the accessions. Results The examined accessions showed significant differences in morphological and pomological aspects (ANOVA, p < 0.05). Among the accessions, the pH varied from 3.02 (‘G75’) to 3.99 (‘G55’), the soluble solids content changed between 8.19 (‘G108’) and 21.98 °Brix (‘G1’), the titratable acidity ranged from 0.69 (‘G3’) to 2.29% (‘G37’), and the ripening index varied from 4.33 (‘G107’) to 29.90 (‘G3’). Principal component analysis (PCA) indicated that fruit traits made the greatest contribution to the diversity among accessions, followed by leaf traits. In the scope of molecular analysis, a total of 195 bands were obtained from 15 inter simple sequence repeat primers (ISSR), and 191 of these bands were found to be polymorphic. The polymorphism rate ranged from 75 to 100%, with an average rate of 97.20%. The similarity index of the accessions ranged from 0.72 to 0.90. According to the quantitative data set, we identified twenty accessions (‘G21’, ‘G117’, ‘G104’, ‘G17’, ‘G11’, ‘G124’, ‘G23’, ‘G10’, ‘G125’, ‘G30’, ‘G2’, ‘G38’, ‘G115’, ‘G4’, ‘G111’, ‘G8’, ‘G35’, ‘G106’, ‘G97’, and ‘G52’, respectively) with superior qualities that can be used as parents in breeding programs or selected directly for cultivation. Conclusions It is believed that the findings from the studied accessions will provide valuable guidance for researchers aiming to understand the characteristics of hawthorn species and incorporate relevant genetic material or traits into modern plant breeding programs. In addition, the study is expected to make significant contributions to the literature on the evaluation and conservation of hawthorn genetic resources.